[PP.16.15] THE RELATION BETWEEN PULSATILE (STIFFNESS RELATED) AND STEADY BLOOD PRESSURE COMPONENTS AND LEFT ATRIAL VOLUME IN THE CONTEXT OF LEFT VENTRICULAR MASS INDEX. (September 2016) - Rojek, M.; Rajzer, M.; Gasowski, J.; Pizon, T.; Czarnecka, D.
Abstract : Objective: To verify the relation between a range of blood pressure components (steady and pulsatile) and carotid-femoral pulse wave velocity and measures of left atrial volume. Design and method: In a group of inhabitants of suburban area of Krakow, we measured 24 hour (SBP24 h, DBP24 h, MAP24 h, PP24 h) and central (cSBP, cDBP, cMAP, cPP) blood pressures and carotid-femoral pulse wave velocity (PWV), parameters of left ventricular mass (LVM, LVMI) and left atrial volume (LAV, LAVI), and gathered anthropometric data, information on habits and relevant medical history. Further, with division according to sex-stratified dichotomised LVMI (95 g/m 2 for women and 115 g/m2 for men) we performed correlation analysis to identify possibly significant relations between measures of left atrial volume and other studied parameters. We also fitted linear regression models in order to assess the respective value of steady and pulsatile BP components as factors related to measures of left atrial volume. Results: The mean (SD) age of 205 participants (66% women, 50% hypertensives) was 53.6 years(±8.3). After group division we identified statistically significant correlations (p < 0.05) only in persons below the group-median value of LVMI. For LAV they were as follows: SBP24h(r = 0.26), MAP24h(r = 0.16), PP24h(r = 0.28), cSBP(r = 0.33), cDBP(r = 0.29), cMAP(0.34), cPP(r = 0.20), PWV(r = 0.25). For LAVI the values were the following: SBP24h(r = 0.24), PP24h(r = 0.28), cSBP(r = 0.34), cDBP(r = 0.30), cMAP(r = 0.32), cPP(r = 0.25), PWV(r = 0.28). In the regression analysis, MAP, and not PP, SBP and PWV, both from 24 h and pulse wave analysis, is related with left atrial volume, in persons below the group-median value of LVMI(p < 0, 05). For LAV: beta = 0.35 for cMAP and beta = 0.35 for MAP24 h. For LAVI: beta = 0.13 for cMAP. In persons with significant increase in LVMI there was no relation between BPs and PWV and left atrial volume measures. Conclusions: Contrary to current knowledge underlying the role of stiffness related BPs in the hard and intermediate outcomes, we found that mean arterial pressure is associated with greater left atrial volumes. The fact that the relation is blunted in persons with greater LVMI, itself related more to MAP than PP, shows the importance of this particular form of target organ damage in relation to LAV.